The Central East Jordan Valley in the Late Bronze and Early Iron Ages - van der Steen, Eveline J. (1996)
The Deir ʿAlla region in the Central East Jordan Valley was relatively densely settled in the Late Bronze Age. Archaeological and other sources suggest that it connected western Palestine with the Transjordanian Plateau in that period. The decline of the Egyptian empire and the collapse of the trade network at the end of the period resulted in the disintegration of this west-to-east route, and of the socioeconomic structure it supported. The result was a return to a more egalitarian society based on agriculture and pastoralism, and settlement of marginal areas. People migrated from the plateau through the Wadi Zerqa and settled in the Jordan Valley. Some may have crossed the Jordan and settled on the other side.